Lower Silurian “hot shales” in Jordan: a new depositional model - Loydell, David; Butcher, Anthony; Fryda, J.; Luning, S.; Fowler, Mike (Journal of Petroleum Geology, 2009)
Data are presented from the Batra Formation (also known as the Mudawwara Shale Formation) of a core from well BG-14 in the Batna el Ghoul area, southern Jordan, which enable a new depositional model to be proposed for the middle Rhuddanian (lower Llandovery, Silurian) “hot shale” which may be applicable to other Arabian and North African “hot shales” of similar stratigraphical age. This “hot shale” probably results from rapid early burial of organic carbon associated with a minor regression during which anoxic bottom conditions were maintained for most, but not all, of the time. Evidence for regression comes from (1) increased sediment grain size within the “hot shale” by comparison with underlying shales; (2) palynological changes including a decrease in acritarch species diversity; an increase in the relative abundance of sphaeromorphs, veryhachiids with three processes and acritarchs with short, simple processes; and a decrease in the relative abundance of acanthomorphs; (3) a positive δ13Corg excursion (other Late Ordovician and Silurian positive δ13Corg excursions occur during regressions); and (4) very brief intervals of oxygenation (associated with sediment influx) reflected in the preservation of graptolites as three-dimensional pyrite internal moulds, rather than as flattened periderm. The minor regression reflects a eustatic sea-level fall, evidence for which has recently been presented from several regions, including Arctic Canada, Bohemia and Scotland. The BG-14 “hot shale” is shown to be thicker than estimated in previous studies. Previous TOC measurements from the upper part of the “hot shale” were affected by the weathering of overlying strata in the BG-14 core. ICP-MS measurements show that uranium content is high in these weathered levels, extending the stratigraphical extent of the “hot shale” interval into the middle Rhuddanian. Depositional models such as that presented here rely on a robust biostratigraphical framework; in the Ordovician and Silurian of Arabia and North Africa, this can be provided by graptolites and chitinozoans.